MODEL INTEGRATIF KEBIJAKAN MONETER ISLAM BERBASIS MAQASHID SYARIAH MEWUJUDKAN STABILITAS EKONOMI BERKELANJUTAN - Violin Ladies Aulia; Ahmad Suminto (LPPM Universitas KH. A. Wahab Hasbullah, 2026)
Monetary policy plays an important role in maintaining economic stability. However, conventional monetary systems based on interest rates are often viewed as vulnerable to financial crises and distributive inequality. Islamic economics offers an alternative through Sharia-based monetary policy that emphasizes justice and social welfare. This study aims to analyze the construction of Islamic monetary policy from the maqashid shariah perspective and examine its managerial and contemporary applications. Using a qualitative literature review approach, the study finds that Islamic monetary policy can be developed through an integrative model linking maqashid shariah, monetary instruments, institutional governance, and welfare outcomes. Its main objectives include protection of wealth, distributive justice, and falah, implemented through sukuk, zakat, productive waqf, and profit-sharing. In Indonesia, implementation has progressed, although challenges remain in instruments, financial dualism, and literacy. Keywords: Islamic monetary policy, Maqhasid shariah, Monetary management, Economic stability, Islamic economic.